2024
DOI: 10.3389/fnagi.2024.1414956
|View full text |Cite
|
Sign up to set email alerts
|

P-hydroxybenzaldehyde protects Caenorhabditis elegans from oxidative stress and β-amyloid toxicity

Xingzhi Yu,
Jie Tao,
Tian Xiao
et al.

Abstract: IntroductionGastrodia elata is the dried tuber of the orchid Gastrodia elata Bl. It is considered a food consisting of a source of precious medicinal herbs, whose chemical composition is relatively rich. Gastrodia elata and its extracted fractions have been shown to have neuroprotective effects. P-hydroxybenzaldehyde (p-HBA), as one of the main active components of Gastrodia elata, has anti-inflammatory, antioxidative stress, and cerebral protective effects, which has potential for the treatment of Alzheimer’s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 103 publications
0
1
0
Order By: Relevance
“…Data from previous studies suggested Gastrodia elata Blume (tianma) may be used as a potential complementary therapy for AD ( Heese, 2020 ). P-hydroxybenzaldehyde (p-HBA), one of the major active components of Gastrodia elata, had a therapeutic effect on AD by alleviating Aβ-induced toxicity via enhancing antioxidant and anti-aging activities and inhibiting Aβ aggregation, as well as enhancing anti-oxidative stress ( Yu et al, 2024 ). A bioactivity test showed that a polysaccharide from Gastrodia elata, named GEP-1, could modulate gut microbiota by promoting the growth of A. muciniphila (A. muciniphila) and Lacticaseibacillus paracasei (L.paracasei) strains ( Huo et al, 2021 ).…”
Section: Herbal Medicine and Admentioning
confidence: 99%
“…Data from previous studies suggested Gastrodia elata Blume (tianma) may be used as a potential complementary therapy for AD ( Heese, 2020 ). P-hydroxybenzaldehyde (p-HBA), one of the major active components of Gastrodia elata, had a therapeutic effect on AD by alleviating Aβ-induced toxicity via enhancing antioxidant and anti-aging activities and inhibiting Aβ aggregation, as well as enhancing anti-oxidative stress ( Yu et al, 2024 ). A bioactivity test showed that a polysaccharide from Gastrodia elata, named GEP-1, could modulate gut microbiota by promoting the growth of A. muciniphila (A. muciniphila) and Lacticaseibacillus paracasei (L.paracasei) strains ( Huo et al, 2021 ).…”
Section: Herbal Medicine and Admentioning
confidence: 99%